Avidity of antibodies against released proteins of Yersinia spp: comparison of patients with or without reactive arthritis. Issue 12 (December 1989) - Lahesmaa-Rantala, R; Heesemann, J; Lehtonen, O P; Granfors, K; Toivanen, A
Abstract : The avidity of IgM, IgG, and IgA class antibodies against virulence plasmid encoded proteins of yersinia, so called released proteins (RPs), was studied in the serum samples of 22 patients with yersinia triggered reactive arthritis and 22 with uncomplicated yersiniosis. The avidity of anti-RP antibodies did not differ significantly between the patient groups, even though the total amount of IgA class anti-RP antibodies was significantly higher in patients with arthritis than in those with uncomplicated yersiniosis at the early stage of infection. Earlier results with whole bacterial extracts or lipopolysaccharide as the antigens have shown an increased avidity of IgA class anti-yersinia antibodies in patients with yersinia triggered reactive arthritis. This phenomenon was not observed in antibody response against RPs, and thus production of these proteins seems unimportant at later stages of infection for the yersinia organisms stimulating the persisting and maturing antibody response in the yersinia triggered reactive arthritis.